2008
DOI: 10.1007/s11426-008-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

Species transformation and structure variation of fulvic acid during ozonation

Abstract: The species transformation and structure variation of fulvic acid (FA) during ozonation were investigated in this study. The molecular weight (MW) distribution, the species of intermediate products and the variation of polar functional groups were studied by ultrafiltration, gas chromatography/mass spectrometry (GC/MS) and titration analyses respectively. The average MW of FA decreased significantly during ozonation. The amount of polar functional groups (carboxylic and phenolic (ph-OH) groups) per unit DOC (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This hypothesis agrees with the measured gas phase emission of formaldehyde, methanol, acetone (or propanal) and acetaldehyde observed upon photolysis under weak near-UV conditions of humic acid films using PTR MS. 19 However, it is in contrast with previous studies on humic acids reactivity in water, where decarboxylation was suggested as the major carbon loss pathway. 38,39 Nitro functions (RÀNO 2 ) show a behavior similar to acidic functions, as their carbon contribution drops from 1.3 to 0.5%, whereas the contribution of carbonyl functions only slightly increases.…”
Section: Hulis T Initial Characterization and Aging Experimentmentioning
confidence: 97%
“…This hypothesis agrees with the measured gas phase emission of formaldehyde, methanol, acetone (or propanal) and acetaldehyde observed upon photolysis under weak near-UV conditions of humic acid films using PTR MS. 19 However, it is in contrast with previous studies on humic acids reactivity in water, where decarboxylation was suggested as the major carbon loss pathway. 38,39 Nitro functions (RÀNO 2 ) show a behavior similar to acidic functions, as their carbon contribution drops from 1.3 to 0.5%, whereas the contribution of carbonyl functions only slightly increases.…”
Section: Hulis T Initial Characterization and Aging Experimentmentioning
confidence: 97%